Implementasi Keamanan Aset Informasi Steganografi Menggunakan Metode Least Significant Bit (LSB) - Abdillah, Muhammad Oemar; Pane, Ogie Ariansah; Lubis, Farhan Rusdy Asyhary (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
Data security is an important factor in electronic transactions because data is sent should be known only to those who are authorized to receive information. Many aspects of data security must be maintained, such as: authenticity, integrity, non-rejection, authority, security, privacy, and access control. The purpose of this study is to create a security system in protecting data and access that requires system security. The process in this study is the creation of an Encoder and Decoder application where in this Encoder Process we insert an image then we set the pixel size and insert Text in the image. At the Decoder stage an image that has gone through the previous Encoder Process can be displayed again to see the result of the Text inserted in the image.